(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
There has been a lot of research into medical facilities and technological developments during the last ten years. To be more specific, the Internet (IoT) has shown promise in connecting a range of healthcare gear, monitors, and hospital professionals in order to provide high medical treatment at a remote location. Patient safety has increased, medical costs have fallen, medical solutions have becoming increasingly available, and efficiency in the healthcare business has increased. The current study presents an up-to-date review of the potential healthcare uses of IoT-based technology. This article describes the advancement of the utilization of the Hospital IoT in solving various healthcare challenges from the perspectives of enabling technology, medical providers, and applications. Furthermore, potential Healthcare IoT system problems and issues are addressed. To summarize, the current research provides a comprehensive resource of knowledge on the different applications of Healthcare IoT, with the purpose of aiding future academics engaged in studying in the area to have a better understanding of the issue.